1998
DOI: 10.1037/0022-006x.66.3.521
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of adaptation in pediatric chronic illness: The importance of the individual.

Abstract: This study used individual growth modeling to examine individual difference and group difference models of adaptation. The adaptation of 27 children with juvenile rheumatoid arthritis (JRA) and 40 children with insulin-dependent diabetes mellitus (IDDM) was tracked for 18 months from diagnosis. A control group of 62 healthy children was followed over the same time period. Clustering procedures indicated that child and family adaptation could be described by a number of distinct adaptation trajectories, indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…For the most part, researchers comparing family functioning in families of children with type 1 diabetes to that of families with physically healthy children found few to no significant differences on domains of family functioning. [21][22][23] Similar to researchers investigating family functioning in families with a child with CF, research investigating families of children with type 1 diabetes found that mothers of children with diabetes reported having less time to engage in activities with their children as compared to mothers of physically healthy children. 22 Also consistent with the CF literature, parents of children with type 1 diabetes reported adopting a somewhat differing set of family values as compared to families of physically healthy children.…”
Section: Type 1 Diabetes Similar To Examinations Of Family Functionimentioning
confidence: 93%
See 1 more Smart Citation
“…For the most part, researchers comparing family functioning in families of children with type 1 diabetes to that of families with physically healthy children found few to no significant differences on domains of family functioning. [21][22][23] Similar to researchers investigating family functioning in families with a child with CF, research investigating families of children with type 1 diabetes found that mothers of children with diabetes reported having less time to engage in activities with their children as compared to mothers of physically healthy children. 22 Also consistent with the CF literature, parents of children with type 1 diabetes reported adopting a somewhat differing set of family values as compared to families of physically healthy children.…”
Section: Type 1 Diabetes Similar To Examinations Of Family Functionimentioning
confidence: 93%
“…11,29 Only a few researchers required a specific post-diagnosis time period. 19,21,23 This selection criterion represents a strength in the research, since it allows for some control of functioning difficulties related to adjustment to a recent diagnosis. Researchers have demonstrated that families are typically shocked when their child is first diagnosed with type 1 diabetes.…”
Section: Critical Evaluationmentioning
confidence: 99%
“…Parents of children with chronic illnesses, such as juvenile idiopathic arthritis (JIA), are at increased risk for psychosocial dysfunction (1)(2)(3)(4)(5). However, only a minority of parents appear to experience a significant degree of psychosocial disturbance (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…According to Frank and colleagues (1), "The functioning of the parent appears to have a much greater impact on adaptation to chronic illness and child functioning than utilitarian (e.g., income, education) and disease variables." Reflecting these sentiments, it is suggested that positive maternal adaptation and functioning can be fostered by reducing maternal anxiety (21) and maintaining parents' self-esteem, psychological stability, and social support (1,22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation